Prospects of hydrocarbon exploration in the Laptev sea basin - Yu. V. Shcherbina; V. Yu. Kerimov; N. A. Kas’yanova; V. К. Abdullayeva (Известия высших учебных заведений: Геология и разведка, 2022)
Background. The geological structure of the Laptev Sea basin is characterized by a rift nature, thus providing no favorable conditions for the presence of hydrocarbon accumulations. However, the lack of seismic information and the absence of well drilling indicate an incomplete stage of the basin exploration.Aim. To analyze the results of geological modeling based on structural mapping and to identify promising areas of hydrocarbon exploration. A geological hydrocarbon study of the Laptev Sea basin was carried out in order to recommend areas for licensing, as well as to identify exploration drilling sites and estimate the total initial prospective geological resources according to the conducted numerical basin modeling. To design sedimentation models and predict reservoir properties in the Laptev Sea basin.Materials and methods. The analysis was based on the data retrieved from production reports for individual large objects in the water area. A model developed by Equinor specialists was used for the basin analysis. The results of hydrocarbon system modeling, the prediction of hydrocarbon saturation obtained from sections of two sample profiles while structural mapping of the basement and top of Oligocene-Miocene sediments were used.Results. Prospective areas of accumulation of hydrocarbons and their confinement were determined. The probability of hydrocarbons in non-anticlinal traps was estimated. Priority areas of hydrocarbon exploration within the unallocated subsoil area were identified. Recommendations for further geological exploration across the license area were formulated.Conclusion. Further exploration of the Yuzhno-Laptevomorsky promising area is recommended by means of analyzing the available data, processing of new geophysical data, updating the geological model and designing 3D seismic surveys within the identified promising areas. In addition, 2D seismic surveys at the regional level should be carried out to define the sedimentary boundaries of the Eastern Artic water area.